2016
DOI: 10.1364/ol.41.002017
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond inscription of phase-shifted gratings by overlaid fiber Bragg gratings

Abstract: Two slightly shifted gratings are inscribed, one over the other, in an SMF fiber with a femtosecond laser and a phase mask. The transmission spectrum of the complex structure is similar to that of a phase-shifted grating; yet, the fabrication process is fast and simple compared to standard methods. High-quality semi-phase-shifted gratings with -24  dB transmission loss and <100  pm transmission bandwidth are presented. Their application as highly narrow micro-resonators and notch filters seems feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Alternatively, phase-shifted FBGs can be fabricated using infrared (IR) femtosecond (fs) lasers. The primary techniques in this case are based on point-by-point/line-by-line writing [6,14,15] and displacing a uniform phase mask during the inscription [16,17]. Uniform phase masks were also used to produce phase-shifted FBGs when i) a uniform FBG was overexposed in the center [18], ii) the central part of the fs-laser beam was blocked [19] and iii) a uniform FBG was written in a length of fiber that incorporates a fusion splice [20].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, phase-shifted FBGs can be fabricated using infrared (IR) femtosecond (fs) lasers. The primary techniques in this case are based on point-by-point/line-by-line writing [6,14,15] and displacing a uniform phase mask during the inscription [16,17]. Uniform phase masks were also used to produce phase-shifted FBGs when i) a uniform FBG was overexposed in the center [18], ii) the central part of the fs-laser beam was blocked [19] and iii) a uniform FBG was written in a length of fiber that incorporates a fusion splice [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only one uniform PM is used for the whole process. In the past, only two FBGs with a slight wavelength shift were inscribed at the same spot to achieve phase-shifted gratings [11,16,25,26]. In addition, such a grating array of five FBGs can be used to simultaneously measure temperature and or strain of a specific spot with different wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that more neighboring resonant peaks could be obtained in the spectrum by introducing phase changes in the center of grating [ 2 ]. Then, the PS-FBG has received a great deal of attention for its narrow linewidth, multiple channels, and flexible combination, and has been widely used in the fields of optical communication, optical calculation, and optical sensing as an emerging optical passive device [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%